0367 Social Determinants of Black-White Disparities in the Work-Sleep Relationship by Occupational Class: A Sequential Mixed Methods Approach. (27th May 2020) - Jackson, C L; Wright, I; Winful, O T; Feinstein, L; Adams, I
Abstract: Introduction: Although Black adults disproportionately work in lower-wage, lower-skilled jobs and experience short sleep (<7 hours), which has been shown to vary by employment industry and occupation, there is scant literature regarding the influence of the work-sleep relationship on racial/ethnic sleep disparities. Our prior quantitative research based on nationally-representative data revealed a novel finding that the prevalence of short sleep was generally highest at professional occupational classes among Black adults but was the least prevalent among their White counterparts. Methods: To identify reasons for short sleep generally increasing with increasing professional occupations among blacks but decreasing among whites, we conducted a qualitative study using a sequential mixed methods design among Black and White workers across a range of industries and occupations. Occupations were classified as "professional" (e.g., doctors; lawyers) or "non-professional" (e.g., retail; food service). Race-matched trained facilitators conducted 36 focus groups that were homogenous in terms of race-sex/gender-occupational class and 63 one-on-one interviews (N=334 overall participants) using semi-structured interview guides. NVivo software was used to identify themes/patterns. Results: Participants were a mean age of 41 ± 11 years, 42% were men, 58% had an annual income of ≥50, 000, and 57% were professionals. Black professionals overwhelmingly described less informational and emotional support as well as needing to "work twice as hard to get half as far" (i.e., John Henryism) compared to coworkers as potential explanations for work-sleep disparities. Both Black and White professionals identified longstanding social structures, interpersonal discrimination, income disparities, and familial or self-imposed pressures to succeed. White professional women frequently reported experiences with gender discrimination, which - they reported - may intersect with and amplify the effects of racial discrimination among Black women. Regardless of occupational class, Black men additionally described unique stressors (e.g., political climate; finances; police). White men frequently avoided discussing disparities, and the existence of disparities was often denied/questioned by non-professionals across race and sex/gender. Conclusion: Our findings inform future research and interventions designed to illuminate and/or address sleep disparities emanating from the workplace. Support: This work was funded by the Intramural Program at the National Institute of Environmental Health Sciences (Z1AES103325-01).